2019
DOI: 10.1002/1873-3468.13325
|View full text |Cite
|
Sign up to set email alerts
|

Generation of mesothelial progenitor‐like cells from mouse‐induced pluripotent stem cells

Abstract: Mesothelial cells, which cover the surface of visceral organs and serous cavities in mammals, play a crucial role in preventing adhesion. We previously reported that primary mesothelial progenitor cells (MPCs) can not only prevent postoperative adhesion but also promote liver regeneration after hepatectomy. Induced pluripotent stem cells (iPSCs) have the potential to be used for regenerative medicine. Here, we have established a differentiation protocol for mouse iPSC‐derived MPCs (miMPCs) via the exposure to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…We found that HIO serosa formation begins after day 7 of culture and is complete between days 14 and 28. Using this developmental timeline, we applied activators and inhibitors of major signaling pathways known to be involved in mesothelial differentiation or intestinal mesoderm development (Colunga et al, 2019;Dixit et al, 2013;Inagaki et al, 2019;Kolterud et al, 2009;Kruithof et al, 2006;Schlueter et al, 2006;Tian et al, 2015;VanDussen et al, 2012;Verzi and Shivdasani, 2008) using suspension HIOs and assessed their effects on the serosa.…”
Section: Hio Serosa Formation Is Enhanced In Suspension Culturementioning
confidence: 99%
“…We found that HIO serosa formation begins after day 7 of culture and is complete between days 14 and 28. Using this developmental timeline, we applied activators and inhibitors of major signaling pathways known to be involved in mesothelial differentiation or intestinal mesoderm development (Colunga et al, 2019;Dixit et al, 2013;Inagaki et al, 2019;Kolterud et al, 2009;Kruithof et al, 2006;Schlueter et al, 2006;Tian et al, 2015;VanDussen et al, 2012;Verzi and Shivdasani, 2008) using suspension HIOs and assessed their effects on the serosa.…”
Section: Hio Serosa Formation Is Enhanced In Suspension Culturementioning
confidence: 99%
“…The visceral and parietal peritoneum surround the peritoneal cavity [ 19 ]. The peritoneum is covered by a thin layer of mesothelial cells [ 7 , 20 ]. Below the mesothelial cells, the basement membrane and interstitial subcutaneous tissue, including collagen fibers, blood vessels, and fibroblasts, are found [ 21 , 22 ].…”
Section: Characteristics and Functions Of Pmcsmentioning
confidence: 99%
“…The glycocalyx, composed of surfactants, phospholipids, and glycosaminoglycans distributed on top of the microvilli of PMCs, creates a lubricating environment for visceral organ activities [ 20 , 29 , 30 ]. PMCs have epithelial and mesenchymal features and can transform under physiological and pathological conditions [ 6 ].…”
Section: Characteristics and Functions Of Pmcsmentioning
confidence: 99%
See 1 more Smart Citation